Investigating the job satisfaction of healthcare providers at primary healthcare centres in Lebanon: A national cross‐sectional study. (18th June 2017) - Alameddine, Mohamad; Baroud, Maysa; Kharroubi, Samer; Hamadeh, Randa; Ammar, Walid; Shoaib, Hikma; Khodr, Hiba
Abstract: Low job satisfaction is linked to higher staff turnover and intensified shortages in healthcare providers (HCP). This study investigates the level of, and factors associated with, HCP job satisfaction in the national primary healthcare (PHC) network in Lebanon. The study adopts a cross‐sectional design to survey HCP at 99 PHC centres distributed across the country between October 2013 and May 2014. The study questionnaire consisted of four sections: socio‐demographics/professional background, employment characteristics, level of job satisfaction (Measure of Job Satisfaction scale) and level of professional burnout (Maslach Burnout Inventory‐HSS scale). A total of 1, 000 providers completed the questionnaire (75.8% response rate). Bivariate and multivariate regression analyses were used to identify factors significantly associated with job satisfaction. Findings of the study highlight an overall mean job satisfaction score of 3.59 (SD 0.54) indicating that HCP are partially satisfied. Upon further examination, HCP were least satisfied with pay, training and job prospects. Gender, age, career plans, salary, exposure to violence, and level of burnout were significantly associated with the overall level of job satisfaction which was also associated with increased likelihood to quit. Overall, the study highlights how compensation, development and protection of PHC HCP can influence their job satisfaction. Recommendations include the necessity of developing a nationally representative committee, led by the Ministry of Public Health, to examine the policies and remuneration scales within the PHC sector and suggest mechanisms to bridge the pay differential with other sectors. The effective engagement of key stakeholders with the development, organisation and evaluation of professional development programmes offered to HCP in the PHC sector remains crucial. Concerned stakeholders should assess and formulate initiatives and programmes that enrich the physical, psychological and professional well‐being of their HCP. The aforementioned suggestions are necessary to strengthen and sustain PHC HCP and support the provision of universal health coverage to the Lebanese population.